Local Community, Development Management and Transition - Nenad Starc (European Regional Science Association (ERSA), 2004)
The paper deals with development management in a transition country (Croatian case) and focuses on preparation of strategic development documents on regional and local level. Socialist legacy obvious in still existing formal approach to preparation and adoption of development documents is discussed first. Inadequacies of such a practice are observed and analysed including the gap between strategic document production and actual decision making. A participative, goal oriented methodology for preparing development documents is proposed next. Preparation steps are listed on the basis of common methodology required by European Union structural funds. Adjustments necessary to make the methodology applicable in the Croatian socio-economic environment are derived from various case studies. Main steps are described and explained as follows: i) estimation of readiness of potential beneficiaries, ii) kick-off seminar, iii) establishment of development councils and development teams, iv) SWOT analysis, v) participative identification of problems, goals and measures, vi) drafting the programme, vii) harmonisation with political programmes, current development programs and plans and the budget, viii) public hearing, ix) drafting the action plan, x) formal adoption and xi) monitoring and evaluation. Implementation problems are discussed in the remainder. Main observed barriers to a sound programme based local development management are: lack of participation in strategic decision making, lack of institutional considerations in programme preparation, inappropriate management capacity of local governments and, before all, lack of political will to base development management on appropriate documentation. The paper concludes with policy recommendation.
Keywords: 330